THU0566 The Olympic Legacy - Did the 2012 Olympic Games Inspire a Generation of Rheumatology Patients to Exercise?. (23rd January 2014) - Muether, M.; Williamson, L.
Abstract : Background: Exercise is of paramount importance for rheumatology patients, but in practice few patients exercise effectively. The London 2012 Olympic and Paralympic games were seen as a catalyst to increase mass participation in physical activity 1 . Objectives: We studied our patient group to find out if the Olympics inspired them to increase exercise. Methods: Two weeks and two months after the Olympics/Paralympics we invited all outpatients attending rheumatology clinics over three week periods to complete anonymous questionnaires comprised of questions regarding activity levels, lifestyle, motivation, obstacles and attitudes to exercise. Results: 87 questionnaires were completed in the first survey and 85 in the second. The mean patient age was 54.4 years (range 22-87); 93 female. 23 (13%) were current smokers, 64 (37%) were ex-smokers and 93 (54%) never smoked. 78 (45%) patients state that they exercised daily, 51 (30%) weekly, 29 (17%) less than weekly and 14 (8%) patients did not exercise. Types of exercise included walking (84%), swimming (21%) and cycling (15%). 113 (66%) claimed they have never been advised to exercise by a health professional. The most common barriers to exercise were pain (53%), tiredness (44%), lack of time (36%) and lack of motivation (23%). 163 (95%) patients thought exercise to be beneficial; 61 (36%) thought exercise could cause harm. Interviewees rated the importance of exercise on a 10 cm VAS at a mean value of 8.1 (SD 1.8), and their confidence to maintain an exercise programme at a mean value of 6.2 (SD 2.9). After 2 weeks, 11 (13%) patients felt the Olympics/Paralympics had altered their attitudes towards exercising. 5 (6%) increased their amount of exercise having watched Olympics/Paralympics, this subgroup consists of never-smokers only. Their visual analogue scale values the importance of regular exercise significantly higher (p<0.05) than the current smokers. After 2 months, 16 (18%) patients felt the Olympics/Paralympics increased their motivation towards physical activity. 8 (9%) patients increased their amount of exercise since watching the Olympics/Paralympics. They were mostly inspired by athlete's individual stories (69%), demonstration of top sporting levels (25%) and taking part in a big sports festival (6%). 65% of the patients followed the games on the media and 35% attended events actively on the Olympic sites. 17 (20%) of the patients considered themselves physically disabled, 2 (12%) of those felt that the Paralympics motivated them to exercise more. Conclusions: Although the majority (95%) of patients regard exercise as beneficial, more than one third (36%) still thinks it does harm, less than half (45%) exercise daily, mostly just walking. A small minority of patients increased their amount of exercise in response to the London 2012 Olympic and Paralympic games. This figure increased two months after the games from 6% to 9%. Patients were most inspired by athlete's individual stories. These could be used in future to as part of a strategy to promote physical exercise for rheumatology patients. References: Developing a physical activity legacy from the London 2012 Olympic and Paralympic Games: a policy-led systematic review; Mike Weed, Esther Coren, Jo Fiore, Ian Wellard, Louise Mansfield, Dikaia Chatziefstathiou and Suzanne Dowse; Perspectives in Public Health 2012 132: 75 Disclosure of Interest: None Declared